2018
DOI: 10.1515/cppm-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pin-Fin Geometry on Microchannel Performance

Abstract: Purpose A numerical analysis is carried out to study the effect of pin fin geometry on the performance of microchannel heat sinks. Design/methodology/approach A three-dimensional numerical analysis is carried out using the conjugate heat transfer module of COMSOL MULTIPHYSICS software. Initially, the study is carried out for a microchannel heat sink with elliptical pin fins of 500 µm fin height, and the results of the same are validated with the results obtained from the literature. Further, the effect of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Heat Sink is an electronic part or gadget of an electronic circuit which scatters heat from different segments (primarily from the power transistors) of a circuit into the encompassing medium and cools them for improving the execution, unwavering quality and furthermore maintains a strategic distance from the untimely disappointment of segments. For the cooling reason, it fuses a fan or cooling gadget [1][2][3][4][5].…”
Section: Heat Sinkmentioning
confidence: 99%
“…Heat Sink is an electronic part or gadget of an electronic circuit which scatters heat from different segments (primarily from the power transistors) of a circuit into the encompassing medium and cools them for improving the execution, unwavering quality and furthermore maintains a strategic distance from the untimely disappointment of segments. For the cooling reason, it fuses a fan or cooling gadget [1][2][3][4][5].…”
Section: Heat Sinkmentioning
confidence: 99%
“…Jadhav et al [14] performed a numerical investigation of the effect of different pin fin shapes (ellipse, circle, square, and hexagon) on a micro-channel. They concluded that for fin pins at larger height and at high coolant inlet flow velocities, the Nusselt number increased.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the impact of increasing nanofluid concentration on heat performance is more important, especially during an increase in Reynolds number. Jadhav et al [4] performed a numerical investigation of the effect of different pin fin shapes (ellipse, circle, square, and hexagon) on microchannel. They concluded that for fin pins at larger height and at high flow coolant inlet velocities, the values of Nusselt number increases.…”
Section: Introductionmentioning
confidence: 99%